Nothobranchius nikiforovi, a new species of seasonal killifish from the lower Matandu drainage in south-eastern coastal Tanzania (Cyprinodontiformes: Nothobranchiidae) - Nagy, Béla; Watters, Brian R.; Raspopova, Alexandra A. (Zootaxa, 2021)
Nothobranchius nikiforovi, a new species known from seasonal habitats in the lower Matandu drainage in south-eastern coastal Tanzania is described. It is distinguished from all other congeners, except N. eggersi, by males presenting two colour phenotypes: the blue phenotype having a bright iridescent light blue to blue-green body, with narrow red-brown scale margins creating irregular reticulated pattern, forming chevron-shaped crossbars on the posteroventral portion of body and light blue median fins with red-brown dotted pattern; the red phenotype has a dark red head, light blue dorsal and anal fins proximally and medially, dark red distally, with dark red stripes parallel to the fin rays, and a plain dark red caudal fin. Nothobranchius nikiforovi differs from N. eggersi by male colour pattern, the blue phenotypes having median fins with dark grey distal portion, some of the rays of dorsal and anal fins with white tips (vs. median fins with distinct slender white distal band), and the caudal fin lacking a spotted pattern (vs. dots arranged into irregular curved stripes); the red phenotype with golden stripe between the nape and dorsal-fin origin (vs. light-blue stripe), the dorsal and anal fins with a plain red distal portion and lacking a light distal band (vs. with distinct narrow white distal band), the pelvic fin lacking a distal band (vs. with distinct slender light blue to white distal band), and some morphometric differences. Phylogenetic analyses also support the genetic distinction of the new species from its closest known relative, N. eggersi, and confirm its position in the N. guentheri species group within the Adiniops subgenus.